Serum Chromium is Inversely Correlated with the Carotid Intima– Media Thickness in Type 2 Diabetic Subjects - Qureshi, Fatima; Khoharo, Haji Khan (Iranian journal of diabetes and obesity, 2023)
Objective: The aim of this study was to determine and correlate the serum chromium in Carotid intima - media thickness (CIMT) in type 2 Diabetes Mellitus (T2DM) subjects. Materials and Methods: The present case – control study included 40 healthy controls and 45 T2DM subjects that were selected through non-probability (purposive) sampling by prior inclusion and exclusion criteria. Serum chromium (Cr) was detected and measured on inductively coupled “Plasma Optical Emission Spectrophotometer” (ICP- OES)- Carotid artery was examined with a 7.5-MHz linear-array transducer (Siemens Acuson x300) sonography. Data was analyzed by Student’s t test and Chi square test in the SPSS 22.0 (USA). Linear regression model was used for predicting carotid intima media thickness. Level of confidence interval of statistical significance was 95% (P≤ 0.05). Results: Serum Cr in controls and cases was noted 0.873 (± 0.162) and 0.281 (± 0.240) µg/ml (P= 0.001). Serum Cr proved negative correlation with random blood sugar (r= -0.145, P= 0.185), HbA1c (r= -0.145, P= 0.0001) and CIMT (r= -0.730, P= 0.0001). Multiple regression analysis model showed significant association of serum Cr (r= -0.730, P< 0.0001) and HbA1c (r= 0.754, P< 0.0001) with the CIMT. Conclusion: The present study reported serum Cr was inversely correlated with the carotid intima - media thickness that is a marker of atherosclerosis. Cr supplements may be advised to diabetics in clinical management.